2013
DOI: 10.1186/1472-6823-13-39
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and clinical correlates of serum bilirubin concentrations in Japanese men and women

Abstract: BackgroundA considerable interest has been drawn to potential protective effects of bilirubin against oxidative stress-related diseases. Smoking is known to be associated with lower concentrations of serum bilirubin, but other behavioral correlates of serum bilirubin have not been well studied. In this cross-sectional study, we examined the associations of behavioral and clinical factors with serum total bilirubin in Japanese men and women.MethodThe study subjects comprised of 4802 men and 6414 women aged 49–7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 33 publications
1
21
3
Order By: Relevance
“…This is not all together surprising in that epidemiological studies have shown that smokers have lower bilirubin levels than nonsmokers and former smokers (Hopkins et al, 1996; Madhavan et al, 1997; Tanaka et al, 2013; Van Hoydonck et al, 2001; Zucker et al, 2004), possibly through induction of UGT 1A1 by nicotine and/or other constituents of tobacco smoke (van der Bol et al, 2007) which may compensate for alcohol’s effects. However, the differential effects of alcohol on bilirubin concentrations for smokers and nonsmokers in our study must be considered very preliminary given the small sample size and differences in baseline characteristics between smokers and nonsmokers.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This is not all together surprising in that epidemiological studies have shown that smokers have lower bilirubin levels than nonsmokers and former smokers (Hopkins et al, 1996; Madhavan et al, 1997; Tanaka et al, 2013; Van Hoydonck et al, 2001; Zucker et al, 2004), possibly through induction of UGT 1A1 by nicotine and/or other constituents of tobacco smoke (van der Bol et al, 2007) which may compensate for alcohol’s effects. However, the differential effects of alcohol on bilirubin concentrations for smokers and nonsmokers in our study must be considered very preliminary given the small sample size and differences in baseline characteristics between smokers and nonsmokers.…”
Section: Discussionmentioning
confidence: 95%
“…The positive association of bilirubin concentrations with various favorable health outcomes has been attributed to, but not proven to, be a consequence of it antioxidant properties.Determining whether multiple days of light drinking alcohol would show a cumulative or persistent effect on bilirubin levels is a critical next step. A recent epidemiological study has documented increased bilirubin levels in association with any level of alcohol consumption (Tanaka et al, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This observation is agreeable in the work reported by Zucker et al [4], who observed a mean difference of 0.2 mg/dL in the value measured using in-vitro laboratories technique. This discrepancy may be contributed by factors such as differences in physical activities, body mass index and diet between females and the males as discussed in the work of Tanaka et al [11]. The relatively low standard deviation in the values predicted for males and females given by 0.007 µmol/L and 0.0086 µmol/L, respectively, may indicate the robustness of the proposed quantification approach towards differences in skin pigmentation.…”
Section: Resultsmentioning
confidence: 89%